CAREM Project Status. (16th January 2011) - Magan, H. Boado; Delmastro, D. F.; Markiewicz, M.; Lopasso, E.; Diez, F.; Giménez, M.; Rauschert, A.; Halpert, S.; Chocrón, M.; Dezzutti, J. C.; Pirani, H.; Balbi, C.; et al.
Abstract : CAREM is a CNEA (Comisión Nacional de Energía Atómica) project. This project consists of the development, design, and construction of a small nuclear power plant. First, a prototype of an electrical output of about 27 MW, CAREM 25, will be built in order to validate the innovation of the CAREM concept and then developed to commercial version. After several years of development, the CAREM Project reached such a maturity level that the Argentine government decided on the construction of CAREM prototype. Several activities are ongoing with the purpose of obtaining the construction permit for the CAREM prototype.